The acceptance of e-learning among UiTM Terengganu students at UiTM Terengganu / Jamilah Abdul Rahman, Siti Noorma Muhaiyiddin & Siti Nor Wahida Saat - Abdul Rahman, Jamilah; Muhaiyiddin, Siti Noorma; Saat, Siti Nor Wahida (2012)
The objective of this project paper is to determine the acceptance of e-learning among students UiTM Terengganu. The whole research is conducted at UiTM Terengganu Campus. A questionnaire was designed to examine student’s acceptance and attitude towards e-learning. Data were collected from 250 degree students of UiTM Terengganu Campus who used the e- learning system for their course. The Technology Acceptance Model (TAM) was used as the core framework for analysis while additional constructs were added in order to find a better model to understand student’s acceptance of e-learning technology. A composite model including three constructs which are perceived usefulness, perceived ease of use and attitude toward using e-learning were formed and tested in the study. Current problems of the acceptance of e-learning are determined and these problems had led to the development of three research objectives and research questions. The significance of this study is focus on individual users’ acceptance investigation for the e-learning in universities as an effective learning tool. Through e- learning it can increase student’s awareness of the importance of advanced technology today. Three hypotheses on researchers’ major focus namely perceived usefulness, ease of use, and attitude toward using e-learning. Both of perceived usefulness and ease of use of e-learning are the factors that influence the user’s attitude toward using e-learning. As all of us know, every research had its own limitation in conducting the whole research process. This research is nor excluded from both issues and researchers claimed that variables, place, sample, and generalization of the result are identified limitations.